KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V SEKOLAH DASAR DALAM MENYELESAIKAN SOAL LEVEL C4 TENTANG MATERI DEBIT - Krisna Anggraeni Susila Saepul Rohman, - (2020)
The purpose of this study is to describe the mathematical problem solving abilities of fifth grade elementary school students in solving c4 level questions about discharge or volumetric flow rate material from various levels of ability. This research is motivated by the low ability of students to solve mathematical problems in solving C4 level problems. The subjects of this study were six students of class V-B at SDN 013 Pasir Kaliki. The research method used is descriptive qualitative research that describes the mathematical problem solving abilities of fifth grade students who have high, medium, and low level abilities in solving C4 level problems according to the way they are, without manipulation during research. Based on research according to George Póly, this study shows the results that students who have high-level mathematical problem solving skills can go through four steps of problem solving. Students who have medium level mathematical problem solving skills are mostly able to go through 3 steps of problem solving and only understand the concept of discharge material, beyond the subject's volume, timing, and discharge's subject. So it is less able to think deeply to solve the problem. Students who have low level mathematical problem solving skills are only able to go through the stage of understanding the problem. The implications for further learning, students with high level abilities are given enrichment, students with moderate level abilities are given remedial, and students with low level abilities are given repetition of material by applying the information processing model. Key word: problems solving and C4 level mathematical questions.